Dinucleotide Sequences at the 5′ Ends of Vaccinia Virus mRNA's Synthesized In Vitro - Keith, Jerry M. (1980)
The diversity of dinucleotide sequences at the 5′ ends of vaccinia virus mRNA's was determined by a two-dimensional electrophoresis procedure. RNA labeled with S-adenosyl[methyl-(3)H]methionine was synthesized in vitro by enzymes present in vaccinia virus cores. The RNA, ending in m(7)G(5′)pppN(m)pN−, was β-eliminated and treated with alkaline phosphatase. After digestion with RNases T(2), T(1), and A, all eight possible dinucleotides containing G(m) and A(m) were identified. They are, in decreasing order of abundance: G(m)pUp (22%), A(m)pCp (18%), G(m)pAp (16%), G(m)pCp (15%), A(m)pAp (11%), A(m)pUp (10%), A(m)pGp (7%), and G(m)pGp (2%).